Pengaruh Intangible Asset, Struktur Modal Dan Return On Asset Terhadap Nilai Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Ibrahim, Ibrahim; Trisalni, Trisalni (Jurnal Unicorn ADPERTISI, 2024)
This research aims to determine the influence of intangible assets on capital structure. And return on assets on company value in manufacturing companies listed on the Indonesian stock exchange for the 2020-2022 period using purposive sampling technique. The population in this research is the financial reports of manufacturing companies listed on the Indonesian Stock Exchange (BEI) in 2020-2022, totaling 241 companies. The research sample used was 68 sample data.The data results of the research variables have been tested using the classic Assumption Test in the form of the Normality, Multicollinearity and Heteroscedasticity Assumption Test. The data analysis method uses multiple linear regression techniques. The results of this research show that intangible assets, structure, capital and return on assets have a significant positive effect on company value in manufacturing companies listed on the Indonesian stock exchange for the 2020-2022 period.